1995
DOI: 10.1093/clinchem/41.11.1585
|View full text |Cite
|
Sign up to set email alerts
|

Relation between cathepsin D expression and other prognostic factors in breast carcinomas

Abstract: We evaluated cathepsin D concentrations in 318 breast carcinoma specimens with a standardized IRMA and established distribution values of 5.9-217.8 nmol/g (median 51.8). Concentrations of cathepsin D did not correlate with age or with concentrations of HER-2/neu oncoprotein, estrogen receptor, or epidermal growth factor receptors. A significant correlation was observed between cathepsin D and progestin receptor (P = 0.009), but only in postmenopausal patients. In our role as a National Reference Laboratory for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The relationship between p185 status and that of Cat D is still controversial. While diverse authors have found a positive association between both variables (Tetu and Brisson, 1994;Eng Tan et al, 1994), others could find no relationship (Isola et al, 1993;Marsigliante et al, 1993;Shaheen et al, 1995). Using quantitative data, we have shown that both parameters are positively correlated (in fact, this was the best correlation obtained in the whole tumor series), and that tumors considered as p185-positive were more frequently positive for Cat D than tumors considered as p185negative.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…The relationship between p185 status and that of Cat D is still controversial. While diverse authors have found a positive association between both variables (Tetu and Brisson, 1994;Eng Tan et al, 1994), others could find no relationship (Isola et al, 1993;Marsigliante et al, 1993;Shaheen et al, 1995). Using quantitative data, we have shown that both parameters are positively correlated (in fact, this was the best correlation obtained in the whole tumor series), and that tumors considered as p185-positive were more frequently positive for Cat D than tumors considered as p185negative.…”
Section: Discussionmentioning
confidence: 48%
“…The HER-2/neu gene status has also been studied in conjunction with other biological prognostic markers, especially with estrogen (ER) and progesterone (PR) receptors, and to a lesser extent with cathepsin D (Cat D) and pS2. While most studies have shown a significant association between p185 overexpression and steroid-receptor negativity (Tandon et al, 1989;Kallioniemi et al, 1991;Ciocca et al, 1992), its relationship with Cat D and pS2 is still controversial (Isola et al, 1993;Tetu and Brisson, 1994;An et al, 1995;Shaheen et al, 1995).…”
mentioning
confidence: 99%
“…The specific binding capacity of EGFR (36) and levels of Cath‐D (37) and c‐erbB‐2 oncoprotein (38) were determined as described earlier.…”
Section: Methodsmentioning
confidence: 99%
“…Reference specimens for the sex-steroid receptors (28) and cathepsin D (29) have been developed earlier as a part of the responsibility of the Hormone Receptor Laboratory as a national reference facility. Specific reference samples made of pooled human tissues containing known quantities of uPA or PAI-1 were produced for this study.…”
Section: Quality Controlmentioning
confidence: 99%